Development of Discovery Learning and Ethnoscience-Based Learning Tools Integrated With Digital Media to Improve the Science Literacy of Elementary School Students - Fita Nelyza; Cut Maulina; Khairus Subula; Melly Fira Yani; Agus Kistian; Putri Nabilah (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
The scientific literacy skills of elementary school students are still low due to less innovative learning and a lack of integration between scientific concepts, local culture, and digital technology. The study aims to develop a learning device based on discovery learning and ethnoscience integrated with digital media to improve elementary school students’ scientific literacy skills. The research employed a research and development method using the ADDIE model (analysis, design, development, implementation, and evaluation). The participants were fifth-grade elementary school students selected based on the characteristics of science learning. Data were collected through expert validation, teacher and student response questionnaires, scientific literacy tests (pretest and posttest), and classroom observations. The validation results showed that the learning device was categorized as “highly feasible” with an average score above 83%. The small group trial indicated that the device was practical and attractive, with a student engagement score of 90% and a digital media attractiveness score of 92%. The field trial revealed a significant improvement in students’ scientific literacy skills, with the average score increasing from 56.6 (pretest) to 81.2 (posttest), resulting in a gain score of 24.6 points. These findings demonstrate that the discovery learning-based and ethnoscience-integrated digital learning device is effective in enhancing students’ scientific literacy. This research supports the implementation of the kurikulum merdeka and contributes to the development of contextual, innovative, and 21st-century-oriented science learning